Anatomical Study of the Dorsal Nasal Artery to Prevent Visual Complications during Dorsal Nasal Augmentation. Issue 11 (16th November 2021) - Tansatit, Tanvaa; Jitaree, Benrita; Uruwan, Sukanya; Rungsawang, Chalermquan
Abstract : Summary: Dorsal nasal augmentation is a common injection associated with ocular complications. Digital compressions on both sides of the nose are recommended during injection. Considering the reported incidences of visual complications, this preventive technique may need an adjustment for more effectiveness to prevent blindness. Therefore, the dorsal nasal arteries (DNAs) were studied by conventional dissections in the subcutaneous and fibromuscular tissues of the nasal dorsum in 60 embalmed cadavers. The results showed that among the 60 faces, 32 faces had bilateral DNAs (53.3%), 23 had dorsal nasal plexus with minute arteries (38.3%), and five had a single dominant DNA (8.3%). The DNA originated from one of the four arterial sources, which influenced the location and course of the artery. These sources included the ophthalmic angular arteries in 21 faces (56.8%), terminal ophthalmic arteries in two faces (5.4%), lateral nasal arteries in 11 faces (29.7%) and facial angular arteries in three faces (8.1%). Consequently, the dominant dorsal nasal artery running close to the midline found in 8% of the cases could make side compressions during nasal dorsum augmentation less effective from preventing ocular complications. However, an adjustment of digital compressions which combines pinching and side compressions is suggested to improve the safety.